Prediksi Luasan Optimal Hutan Kota Sebagai Penyerap Gas Karbondioksida (CO2) di Kota Medan - Suri Fadillah; Siti Latifah; Asep Sukmana (Program studi Kehutanan USU, 2013)
City is the center of government and human activities. The tendency of all activities centered in the city results increasing of city development. This impacts the reduction of Green Open Space especially the urban forest, the increasing of carbondioxide concentration and the reduction of oxygen in the air. Such condition can reduce the urban environment quality, because one of the functions of urban forest is to absorb carbondioxide. This study aims to analyze the needs of urban forest width based on the function of carbondioxide absorber in Medan up to 2050. The method used was by collecting primary and secondary datas, then data analysis was performed to determine the optimal width for urban forest. The results showed that in 2012 Medan city need urban forest width for carbondioxide absorber about 4.304,21 ha and in 2050 is 9.880,06 ha. Keywords: Green Opeh Space, Urban Forest, Carbondioxide, Optimal Width